LBPS 02-37 ADRENAL HEMORRHAGE FOLLOWING ADRENAL VEIN SAMPLING IN PRIMARY ALDOSTERONISM: A SIX-CENTER EXPERIENCE. (September 2016) - Monticone, Silvia; Satoh, Fumitoshi; Dietz, Anna S; Goupil, Remi; Lang, Katharina; Pizzolo, Francesca; Gordon, Richard D; Morimoto, Ryo; Reincke, Martin; Stowasser, Michael; Mulatero, Paolo
Abstract : Objective: Adrenal vein sampling (AVS) is the only reliable means to distinguish between aldosterone-producing adenoma and bilateral adrenal hyperplasia, the two most common subtype of primary aldosteronism (PA). A rare but serious complication of AVS is an adrenal hemorrhage (AH). Design and Method: We retrospectively evaluated 24 cases of AH after AVS that occurred in 6 tertiary referral hypertension centers in Italy, Germany, Japan and Australia. The control group comprised 1388 PA patients who underwent AVS in the different centers participating in the study during a similar period of time as when the patients experienced AH during AVS. Results: In our case-series, AH more often affected the right adrenal (nY=Y18) than the left (nY=Y5, PY<Y0.001); 1 bilateral. Patients experiencing AH were older than patients who underwent uncomplicated AVS procedures. None of the other assessed clinical or biochemical and hormonal parameters were significantly different between the AH and the controls. Median duration of experience of the radiologist in AVS at the time of AH was 5.0 years (0.6-7.8) and AH occurred with both highly experienced (>10 years) and less experienced radiologists. Of 9 AH in the gland contralateral to an aldosterone-producing adenoma and who underwent complete (nY=Y6) or partial (nY=Y3) unilateral adrenalectomy, only one resulted in adrenal insufficiency and the patient required long-term corticosteroid replacement therapy. No reduction in blood pressure or biochemical resolution of PA occurred in any of those patients who experienced AH in the gland ipsilateral to an aldosterone-producing adenoma (nY=Y6) or who had bilateral adrenal hyperplasia (nY=Y9). No patient required blood transfusion or invasive approaches to control bleeding. Conclusions: In conclusion, AH usually has a positive outcome and AVS should remain the preferred approach to subtype differentiation in PA patients.